Social Skills of Elderly Prisoners Perpetrators of Pedophilia - Nurhadi Muhammad Sukry; Beatrek Agel; Andrew Wely (World Psychology, 2022)
Increasing age triggers a decrease in the production of the hormone testosterone, thus affecting a person's sexual ability. Although, in theory, there is a sexual decline in the elderly, in reality, there are still older adults whose sexual desires are still strong and even commit sexual deviations. This study aimed to determine the cause of pedophilia seen from the social skills of elderly inmates at the Class II B Correctional Institution Muaro Sijunjung. The type of research in this study is qualitative research with a phenomenological approach. The research subjects were three elderly prisoners with child protection cases aged sixty years and over. The instrument in this research is the researcher himself. The collection techniques in this study were interviews and documents. The data analysis technique in the research that the researcher did was to systematically search and compile the data obtained from the interviews and documents to make the findings easy to understand and well-informed. The data analysis process starts from the process of making verbatim and coding. To test the validity of the data that has been obtained so that it fits the research objectives, the researcher uses the triangulation method. The triangulation used in this study is triangulation with sources, namely comparing and checking the level of certainty of data obtained through time and various devices in qualitative methods. From research in the field, it can be concluded that the cause of pedophile perpetrators is due to divorce, poor relationships with partners, and past abuse, causing pedophilic sexual deviant behavior. This study also looks at behavioral symptoms from four aspects of elderly social skills: Environmental Behavior, Interpersonal Behavior, Self Related Behavior, and Task Related Behavior.